[BP.11.02] ALCOHOL INTAKE MORE THAN DOUBLES THE RISK OF EARLY CARDIOVASCULAR EVENTS IN YOUNG HYPERTENSIVE SMOKERS. (September 2017) - Mos, L.; Saladini, F.; Fania, C.; Mazzer, A.; Garavelli, G.; Palatini, P.
Abstract : Objective: Little information is available on the joint effect of smoking and alcohol on major adverse cardiovascular and renal events (MACE) in hypertension. Aim of the study was to quantify the interactive effect of smoking and alcohol intake on MACE in young subjects screened for stage 1 hypertension. Design and method: A total of 1204 untreated patients aged from 18 to 45 years (mean 33.1 ± 8.5) were included in this prospective cohort study. Subjects were classified into 4 classes of smoking and 3 classes of alcohol use. Main outcome variable was risk for MACE. A parsimonious set of covariates was selected using sequential backward elimination of the least significant variables. Subsequently, a final model was developed in which lifestyle factor category was entered as the first variable and then was adjusted for other risk factors and several confounders. Results: During a 12.6-year follow-up there were 74 fatal and nonfatal MACE. In multivariable Cox models there was a linear relationship of smoking and alcohol drinking with risk of MACE. Hazard ratio was 1.65 (95% CI, 1.35–2.02, p < 0.0001) for smoking and was 2.05 (95%CI, 1.22–3.43, p = 0.007) for alcohol use. In addition, a strong interactive effect was found between smoking and alcohol on risk of MACE (p < 0.0001). Among the 142 smokers who also drank alcoholic beverages the risk of MACE (4.02, 95%CI, 1.98–8.15) was more than doubled compared to the 112 smokers who abstained from drinking (1.64, 95%CI, 0.63–4.27). In the group of heavy smokers who also were alcohol drinkers (n = 51) the risk of MACE was even quadrupled. In this group, urinary catecholamines (mean ± SEM, 104.5 ± 13.3 mcg/g versus 70.9 ± 4.1 mcg/g, p = 0.01) and 24 h heart rate (mean ± SEM, 75.7 ± 1.1 versus 72.8 ± 0.2 bpm, p = 0.008) were increased compared with the rest of the cohort. Conclusions: Alcohol use strongly potentiates the deleterious cardiovascular effects of heavy smoking in stage 1 hypertensive subjects younger than 45 years. Increased sympatho-adrenergic activity may be a contributing factor to the synergistic effect of smoking and alcohol on MACE. These results call for prompt intervention addressed to improve unhealthy behaviours in these subjects.